Have cochlear implant, won’t have to travel: introducing telemedicine to people using cochlear implants - Cullington, Helen; Kitterick, Pádraig T.; DeBold, Lisa; Weal, Mark; Clarke, Nicholas; Newberry, Eva; Aubert, Lisa (ASHA, 2016)
Purpose: This paper describes a planned project to design, implement, and evaluate remote care for adults using cochlear implants and compare their outcomes with those following the standard care pathway.Method: Sixty people with cochlear implants will be recruited and randomized to either the remote care group or a control group. The remote care group will use new tools for 6 months: remote and self-monitoring, self-adjustment of device, and a personalized online support tool. The main outcome measure is patient empowerment, with secondary outcomes of hearing and quality of life stability, patient and clinician preference, and use of clinic resources.Conclusion: The clinical trial ends in summer 2016. Remote care may offer a viable method of follow-up for some adults with cochlear implants.